Book review: eds. Romulo Pinheiro, Maria Laura Frigotto, Mitchell Young (2022), Towards resilient organizations and societies: a cross-sectoral and multi-disciplinary perspective, Palgrave Macmillian, (eBook) - PROFIROIU Alina-Georgiana (Applied Research in Administrative Sciences)
The book titled “Towards Resilient Organizations and Societies: A Cross-sectoral and Multi-disciplinary Perspective” is part of the series “Public Sector Organizations “, a series that covers issues such as: the methodology for studing public sector’ organizations, the public sector’s autonomy, bureaucratic politics, networks analysis, leadership and organizational change. This volume, edited by Romulo Pinheiro, Maria Laura Frigotto, Mitchell Young, is the result of the panel “The Surprinsing Nature of Resilience Organizations”, held in Tallin, Estonia, hosted by the European Group of Public Administration. Its aim is to offer a holistic and deep understanding of the concept of resilience in order to support public managers from different public organizations, polimakers, local or regional planers, scholars in their effort of pursuing resilience in the context of multiple crises.